Interactive E-Module Based on Scientific Approach in Science Content Learning for Sixth-Grade Students - Lase, Kurnia Sotatema; Sudarma, I Komang (MIMBAR PGSD Undiksha, 2023)
The low science learning outcomes of elementary school students are due to the need for more use of media and teaching materials that can attract students' interest in learning, so to overcome these problems, learning media such as e-modules based on a scientific approach are needed. This study aims to determine the design, feasibility, and effectiveness of scientific approach-based interactive e-modules in learning science content for sixth-grade elementary school students. This research belongs to the type of development research which was developed using the ADDIE model. The subjects involved in this study were 1 subject matter expert test, 1 instructional design expert, 1 instructional media expert, and two product test subjects, namely 3 individual test subjects and 9 small group tryouts. Data collection in the study was carried out using observation, interview, questionnaire, and test methods, with research instruments in the form of expert learning questionnaires and individual and small group trial instruments. The data obtained in the study were then analyzed using qualitative data analysis techniques, quantitative descriptive data analysis, and inferential statistical data analysis techniques (t-test). The results of the data analysis showed that the results of the review by subject content experts obtained a percentage of 85.33% with good qualifications, the results of the review by learning design experts obtained a percentage of 95.71% with very good qualifications, the results of the review by learning media experts obtained a percentage of 92.5 % with very good qualifications, the results of reviews from students through individual trials obtained a percentage of 92% with very good qualifications, and the results of reviews from students through small group trials obtained a percentage of 95.77% with very good qualifications. So, interactive e-module media based on a scientific approach effectively improves science learning outcomes for sixth-grade elementary school students.